การศึกษา รูปแบบความสัมพันธ์เชิงสาเหตุระหว่าง พละ 5 และพฤติกรรมด้านคุณธรรมในมิติของสังคหวัตถุ 4 ของผู้ปฏิบัติกรรมฐานในพุทธศาสนาเถรวาท และความสามารถเชิงปัญญาของผู้นำเชิงกลยุทธ์ในธุรกิจธนาคารพาณิชย์ไทย - ธีรไชยพัฒน์ (Chainarin Teerachaipat) ชัยนรินท์; เผ่าพันธุ์ (Natsapan Paopun) ณัฐสพันธ์; ถุงสุวรรณ (Amorn Thoongsuwan) อมร (Journal of Behavioral Science for Development, 2016)
(A Study of Causal model of Relationship Among Pancabala and the Context of Virtue Behavior in Sangahavatthu in Kammatthana Practitioner in Theravada Buddhism and Intellectual of Strategic Leadership Competency of Thai Banking Manager) Abstract This qualitative research were aims: 1) to identify the level composition factors and the influencing size of the variables of causal model and investigate the congruence of causal model and empirical data. The samples size were 400 by simple random sampling. The instrument were multiple choice and five levels Scale questionnaires. Data were analyzed by using program SPSS version 11.5 and program LISREAL version 8.52 The results of this research were as follow: 1)The variable Satthabala Viriyabala Satibala Samatibala and Panyabala were the composition of Pancabala. The variable Than Piyavaja Atthajariya and Samanatta were the composition of Sangahavatthu. The variable People wisdom Contextual wisdom Procedural wisdom and Outcomes wisdom were the composition of on the Intellectual of Strategic Leadership Competency of Thai banking manager. Statistical analysis results confirmed the research hypotheses of the goodness of fit of structural relationship model showed its consistency with the empirical data. 2)Pancabala and Sangahavatthu could demonstrate the variance of the Intellectual of Strategic Leadership Competency of Thai banking manager respectively. Pancabala has direct positive effect on the Context of Virtue Behavior in Sangahavatthu and the Intellectual of Strategic Leadership Competency of Thai banking manager and the Context of Virtue Behavior in Sangahavatthu has direct positive effect on the Intellectual of Strategic Leadership Competency of Thai banking manager. Pancabala has indirect positive effect and a high level of total effect on the Intellectual of Strategic Leadership Competency of Thai banking manager respectively. Keywords: Pancabala, Kammatthana, Theravada Buddhism, Virtue Behaviour, Sangahavatthu, Virtue Behaviour, Strategic Leadership